Peculiar Features of Gas and Dynamic Mode in Hole Vicinity - S. N. Osipov (Наука и техника)
The paper reveals what role pre-wall zone of rock mass being disturbed due to hole sinking plays in respect of gas inflow (fluid) through hole flank surface. High efficiency of gas permeability increase through rock in the hole vicinity has been determined analytically that leads to significant increase of gas inflow.